SEJARAH TRADISI FILSAFAT HELLENISTIK DALAM ISLAM - Irwan Ahmad Akbar (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2020)
The purpose of this research is to answer how the Greek Hellenistic philosophical tradition can develop into the Islamic world. This research is a descriptive-analytic study of historical data (historical-ontological study). So this research has the conclusion that: Hellenistic philosophical tradition can develop in the world of Islam due to the wide expansion in the areas around Arabia that Islam did, including: during the Sa>ha>bah era where they found the Alexandria library in Egypt, the Umayyads who tended to use the works - Ancient Greek works of practical science, such as medicine and astronomy. It was only during the time of the Abbasids that there was a massive translation of almost all ancient Greek works, especially philosophy. It was at that time that the Hellenistic philosophical tradition in the Islamic world stood at its peak.